Utilitas Konsumen Muslim - Panji Sudono Bekti; Amin Wahyudi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The main motive of a consumption is to obtain a utility/satisfaction. However, in Islam there are many rules of consumption that can be restrict for consumer’s freedom. The purpose of this article is to find out how Islam manages consumer and how a Muslim obtains maximum utility in his consumption. The method of this research is literature study by reviewing books, scientific journals, and articles from relevant official websites. The results of the research shows that Muslim consumer still gets maximum utility even though there are many rules that regulate him. Even, his maximum utility is not influenced by his financial capabilities.